2011
DOI: 10.2166/wst.2011.056
|View full text |Cite
|
Sign up to set email alerts
|

The role of colloidal and particulate organic compounds in denitrification and EBPR occurring in a full-scale activated sludge system

Abstract: The efficiencies of denitrification and enhanced biological phosphorus removal (EBPR) in biological nutrient removal (BNR) activated sludge systems are strongly dependent on the availability of appropriate carbon sources. Due to high costs of commercial compounds (such as methanol, ethanol, acetic acid etc.) and acclimation periods (usually) required, the effective use of internal carbon sources for denitrification is preferred. The aim of this study was to determine the immediate effects of slowly biodegradab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…In both cases, the anaerobic hydrolysis of pCOD could not provide significant carbon source for PAOs’ activity in 4 h of anaerobic condition. Drewnowski and Makinia () also reported that the effect of pCOD on anaerobic phosphorous release of activated sludge from two different full scale plants was not significant. Therefore, the very low rate of anaerobic hydrolysis found in these studies might not be due to the specific activated sludge and wastewater tested.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both cases, the anaerobic hydrolysis of pCOD could not provide significant carbon source for PAOs’ activity in 4 h of anaerobic condition. Drewnowski and Makinia () also reported that the effect of pCOD on anaerobic phosphorous release of activated sludge from two different full scale plants was not significant. Therefore, the very low rate of anaerobic hydrolysis found in these studies might not be due to the specific activated sludge and wastewater tested.…”
Section: Resultsmentioning
confidence: 99%
“…The objective of this study was to assess the effect of anaerobic hydrolysis of pCOD on phosphorous removal performance. The anaerobic hydrolysis of pCOD was mainly investigated by using kinetic tests with anaerobic condition of about 2 h (Choi and Lee, ; Drewnowski and Makinia, , ; Goel et al, ; Puig et al, ). In this study, the anaerobic HRT was extended to 4 h to assure the potential effect of pCOD under anaerobic condition, even at low level, could be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…volume of 4.0 dm 3 ) and automated control system for temperature and dissolved oxygen (DO) concentration (Drewnowski and Makinia, 2011). The reactors were equipped with probes/electrodes (WTW GmbH, Germany) for continuous monitoring of pH (SenTix 21), oxidation-reduction potential (ORP) (SenTix ORP), temperature and DO concentration (CellOx 325).…”
Section: Laboratory Apparatusmentioning
confidence: 99%
“…For this purpose, Drewnowski and Makinia (2011) developed and implemented a novel procedure based on the standard batch experiments and pre-treatment of settled wastewater sample. In this follow-up study, these effects were comprehensively evaluated with respect to denitrification, phosphate release/uptake and oxygen utilization for a fullscale process mixed liquor originating from two large BNR WWTPs in northern Poland.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some SBOM were removed along with the sedimentation of floating matter, and thus, some dissolved organic carbon source adsorbed on the particulate matter were removed along with the sedimentation of particulate matter. Drewnowski and Makinia (2011) pointed out that the removal of particulate organic matter in the primary settling tank decreases the anaerobic phosphorus release rate and anoxic phosphorus uptake rate by 14% and 46%, respectively. Therefore, large amounts of carbon are wasted in the primary settling tank, which intensifies the shortage of carbon source, ultimately impacting the nitrogen and phosphorus removal in the biological tank.…”
Section: Loss Of Carbon Source In Primary Treatment Systemsmentioning
confidence: 99%